Analytical Separation Science 2015
DOI: 10.1002/9783527678129.assep025
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Detectors in Gas Chromatography

Abstract: The aim of this chapter is to provide basic interpretation of gas chromatography ( GC ) detectors mainly devoted to the students and beginners in the field of GC .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In FID, the column effluent is combusted by an air‐hydrogen flame, causing ionization of compounds and producing a current which is detected and converted to a signal. FIDs are widely used due to low cost, long‐term reliability, and universal applicability for compounds with carbon‐hydrogen bonds in their chemical structure (Mariaca, & Bosset, ; Rahman, El‐Aty, & Shim, ).…”
Section: Dynamic Extractions – Purge and Trap Thermal Desorption Somentioning
confidence: 99%
See 2 more Smart Citations
“…In FID, the column effluent is combusted by an air‐hydrogen flame, causing ionization of compounds and producing a current which is detected and converted to a signal. FIDs are widely used due to low cost, long‐term reliability, and universal applicability for compounds with carbon‐hydrogen bonds in their chemical structure (Mariaca, & Bosset, ; Rahman, El‐Aty, & Shim, ).…”
Section: Dynamic Extractions – Purge and Trap Thermal Desorption Somentioning
confidence: 99%
“…Each adjacent rod has the opposite charge compared to its nearest counterpart. When DC voltage is applied and the voltage signs are rapidly reversed, varying electrical fields are produced, enabling ions with specific mass‐to‐charge ratios to pass (Rahman et al., ).…”
Section: Dynamic Extractions – Purge and Trap Thermal Desorption Somentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that GC is more suitable for volatile compounds in comparison to LC which is applied to more polar and non-volatile compounds (Chormey, Karakuş, et al, 2017). GC can be coupled with different detection systems including thermal conductivity detector (TCD), electron capture detector (ECD), nitrogen phosphorus detector (NPD) and flame photometric detector (PID), flame ionization detector (FID) (Chormey, Büyükpınar, Turak, Komesli, & Bakırdere, 2017;Rahman, El-Aty, & Shim, 2015). A more sensitive, accurate and precise determination of compounds is achieved when GC is coupled with mass spectrometry (MS) (Lindon, Tranter, & Koppenaal, 2016).…”
Section: Introductionmentioning
confidence: 99%